2008
DOI: 10.1021/es070895g
|View full text |Cite
|
Sign up to set email alerts
|

Are PFCAs Bioaccumulative? A Critical Review and Comparison with Regulatory Criteria and Persistent Lipophilic Compounds

Abstract: Perfluorinated acids, including perfluorinated carboxylates (PFCAs), and perfluorinated sulfonates (PFASs), are environmentally persistent and have been detected in a variety of wildlife across the globe. The most commonly detected PFAS, perfluorooctane sulfonate (PFOS), has been classified as a persistent and bioaccumulative substance. Similarities in chemical structure and environmental behavior of PFOS and the PFCAs that have been detected in wildlife have generated concerns about the bioaccumulation potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
659
4
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,012 publications
(701 citation statements)
references
References 51 publications
(137 reference statements)
36
659
4
2
Order By: Relevance
“…In addition, PFHxA and PFHpA considerably modulated the expression levels of various tissue-specific genes that were relevant to the observed external and internal phenotypes. In particular, xPTB was used as a liver-specific marker and the protein encoded by this gene complexes with the LDL receptor to mediate hepatic LDL removal by endocytosis (35,36). Consistent with other reports, the xPTB mRNA levels were considerably modulated following exposure to either PFHxA or PFHpA (16).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, PFHxA and PFHpA considerably modulated the expression levels of various tissue-specific genes that were relevant to the observed external and internal phenotypes. In particular, xPTB was used as a liver-specific marker and the protein encoded by this gene complexes with the LDL receptor to mediate hepatic LDL removal by endocytosis (35,36). Consistent with other reports, the xPTB mRNA levels were considerably modulated following exposure to either PFHxA or PFHpA (16).…”
Section: Discussionsupporting
confidence: 80%
“…Several studies have examined the toxicity of different PFC in many aquatic and other animals (24,32,33). These studies have confirmed that exposure during particular developmental stages or under certain nutritional conditions produced adverse effects on neonates (34,35). Amphibians are more sensitive to environmental exposures during the fetal stage.…”
Section: Discussionmentioning
confidence: 97%
“…51 Because of the lack of a suitable normalization criteria for PFASs, such as total lipid weight for neutral organic chemicals, BAFs have sometimes been reported for individual tissues. 16 Median log BAF tissue values for F-53B varied considerably among the different tissues, ranging from 3.80 to 5.23 for TL, and 3.92 to 5.01 for XR, but were consistently higher than ones for PFOS (see also Table S10). However, for assessment of the bioaccumulation potential compared to regulatory criteria, whole body concentrations should be used because concentrations in most measured tissues would overestimate bioaccumulation potential.…”
Section: Environmental Science and Technologymentioning
confidence: 96%
“…16 Unlike most persistent organic pollutants, perfluoroalkyl acids do not partition into storage lipids due to the dipolar nature of the carbon−fluorine bond and their anionic headgroup. 16 Instead, specific protein-binding mechanisms and/or partitioning to phospholipids have been proposed to explain the surprisingly high bioaccumulation potential of some PFASs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…pressure 0.49 MPa and pH 1.5. PFOA is more widely detected in the environment than other PFCAs, and bioaccumulation of PFCAs is directly related to length of perfluorinated carbon-chain [29,30]. It is more necessary and valuable to know whether and how PFOA is decomposed.…”
Section: Introductionmentioning
confidence: 99%